Dual processing of R-loops and topoisomerase I induces transcription-dependent DNA double-strand breaks - Cristini, A; Ricci, G; Britton, S; Salimbeni, S; Huang, S; Marinello, J; Calsou, P; Pommier, Y; Favre, G; Capranico, G; Gromak, N; Sordet, O (Elsevier, 2019)
Although accumulation of DNA damage and genomic instability in resting cells can cause neurodegenerative disorders, our understanding of how transcription produces DNA double-strand breaks (DSBs) is limited. Transcription-blocking topoisomerase I cleavage complexes (TOP1ccs) are frequent events that prime DSB production in non-replicating cells. Here, we report a mechanism of their formation by showing that they arise from two nearby single-strand breaks (SSBs) on opposing DNA strands: one SSB from the removal of transcription-blocking TOP1ccs by the TDP1 pathway and the other from the cleavage of R-loops by endonucleases, including XPF, XPG, and FEN1. Genetic defects in TOP1cc removal (TDP1, PNKP, and XRCC1) or in the resolution of R-loops (SETX) enhance DSB formation and prevent their repair. Such deficiencies cause neurological disorders. Owing to the high frequency of TOP1cc trapping and the widespread distribution of R-loops, these persistent transcriptional DSBs could accumulate over time in neuronal cells, contributing to the neurodegenerative diseases.